IDENTIFICATION OF DENOTATION CONNOTATION AND MYTH IN THE FIGURE OF MARIA MAGDALENE ON THE DA VINCI CODE DAN BROWN.docx - Purwa Bintang Sabilillah; Myrna Nur Sakinah (Universitas Muhammadiyah Surakarta, 2019)
This research discusses discoveries, denotatives, connotatives and myths in literary works, a novel entitled The Da Vinci Code by Dan Brown. The theory used is the concept of semiotics according to Roland Barthes who proposed the concept of the developed theory from Ferdinand de Saussure developed by Barthes which was designed to determine denotatives, connotative and myth to the theory which means a way of interpreting fiction and non-fiction. Because the object of this research is a written work (fiction), no field survey was carried out and only library research. The subject of the author's focus is Denotative, Connotative and Myth that appear in the figure of Mary Magdalene narrated in this novel. Documentation is used with the terms of findings and savings the datum that consider as the one that can be identified and analyzied by the researchers. The researchers try to open, analyse and describe the figure of Mary Magdalene that is related with Christianity, Jesus and the Holy Grail using Barthes. The result or the output of the research is that there are five data containing and considering as the example of Barthes concept of Denotation, Connotatioan dan Myth with several reasonings. In this case, identifying an object is the figure of Maria Magdalene in the Novel The Da Vinci Code.Keywords: Myth, Maria Magdalene, Holy Grail, Barthes